Congenital optic disc pits and optic disc pit maculopathy: a review - Esmaeil, Ali; Ali, Ali; Almutairi, Salman; Alkandari, Khaled; Behbehani, Raed; Alali, Alaa (Frontiers in Ophthalmology, 2023)
Optic disc pits are a rare but significant anomaly of the optic nerve head that can lead to visual impairment and associated complications. These pits are characterized by a small, oval-shaped depression in the disc, which can cause fluid accumulation and subsequent damage to the adjacent retina. Although the etiology and pathogenesis of optic disc pits are not fully understood, several theories have been proposed, including abnormal embryonic development and degenerative changes. Diagnosis is typically made through a comprehensive eye examination, including a dilated fundus exam and optical coherence tomography. Management options vary depending on the severity of the condition and associated complications, ranging from observation to surgical intervention.